Structural, gelatinization, and rheological properties of heat-moisture treated potato starch with added salt and its application in potato starch noodles. (October 2022) - Yang, Sha; Dhital, Sushil; Zhang, Meng-Na; Wang, Jie; Chen, Zhi-Gang
Abstract: Gluten-free noodles, e.g. potato starch noodles, are getting popular due to the increasing population with gluten sensitivity and celiac disease. However, due to the lack of gluten network, the solid loss of potato starch noodles during cooking leads to lower textural and sensory attributes. The starch modification provides the opportunity to address these shortcomings. Here, we report the application of heat-moisture treated (HMT) potato starch with added salt as a binder to improve the cooking and textural properties of potato starch noodles. In the presence of sodium tripolyphosphate (STPP) and sodium chloride (SC), starch granules exhibited irregular shapes and deformed crystalline growth rings, agglomerated due to partial gelatinization, and lost double-helical structures and the perfection of crystallites after being subjected to HMT. As affected by the starch-ions interactions and changed water structure, HMT-modified starch with added SC and STPP had higher pasting temperatures, less amylose leaching, and lower gelatinization enthalpies and pasting viscosities than HMT starch without salts. Meanwhile, higher cross-over temperatures and lower G' values were found in HMT starch with added STPP and SC compared to HMT starch. Iodine-staining micrographs also confirmed the delay in the disintegrating process of starch granules in HMT-modified starch with added SC and STPP. Furthermore, when HMT-modified starch with added SC was applied as binder paste, starch dough owned higher hardness and starch noodles exhibited less solid loss and broken noodles, firmer texture, and better elasticity. The results thus provide the opportunity to improve the textural attributes of potato starch noodles with the application of HMT potato starch and salt as the binder. Graphical abstract: Image 1 Highlights: Structural changes of starch before and after HMT as affected by salts are studied. Adding sodium chloride induces the losses of ordered structure of starch during HMT. Adding salts delays the disintegrating of starch granules during gelatinization. HMT starch with added sodium chloride (HPS-SC) has better heat and shear stability. HPS-SC as a binder improves cooking performance and texture of starch noodles.